Small Donor–Acceptor Molecules Based on a Quinoline–Fluorene System with Promising Photovoltaic Properties. Issue 14 (24th April 2016) - Slodek, Aneta; Matussek, Marek; Filapek, Michal; Szafraniec‐Gorol, Grazyna; Szlapa, Agata; Grudzka‐Flak, Iwona; Szczurek, Magdalena; Malecki, Jan Grzegorz; Maron, Anna; Schab‐Balcerzak, Ewa; Nowak, Elzbieta M.; Sanetra, Jerzy; et al.
Abstract: A series of small donor–acceptor (D–A) systems based on quinoline derivatives bearing a fluorenyl motif were synthesized through Ru‐catalyzed reactions. Their photophysical, electrochemical, and structural properties were investigated deeply. The photoluminescence spectra of most of the compounds were characterized by an intense band at λ ≈ 400 nm, whereas a redshifted band occurred at λ = 560 nm if the substituent of the quinoline was changed to the strongly electron‐withdrawing NO2 group. Most of the synthesized compounds exhibited appealing luminescence and electrical properties, which might make them useful materials for photovoltaics. Preliminary electrical conductivity measurements of indium tin oxide/compound/Al devices showed that the current is enhanced as the applied voltage increases and, therefore, proved the semiconducting properties of the investigated compounds. Moreover, one of the synthesized compound was tested as a component of the active layer in a bulk heterojunction (BHJ) solar cell, and a power conversion efficiency (PCE) of 0.25 % was obtained. Abstract : A series of small donor–acceptor systems based on quinoline derivatives bearing a fluorenyl motif are synthesized through Ru‐catalyzed reactions. Most of the synthesized compounds exhibit appealing luminescence, electrical, and thermal properties. A bulk heterojunction (BHJ) solar cell with one of the compounds as a component of the active layer has a power conversion efficiency (PCE) of 0.25 %.